Identities and Roles of Gay and Bisexual Teachers in Rural Philippines - Rick Añonuevo; Gerry Digo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study utilized a descriptive exploratory approach to explore the identities and roles of gay and bisexual teachers in their workplace. The ten informants were purposively chosen. Interviews, focus group discussions, and direct and participant observation were the data-gathering procedures employed in the study. To dig deeper into their identities and roles, thematic analysis was used. The study revealed that the profile of gay and bisexual teachers varied from one another. Further, the informants identify with their preferred gender identities and characterize their roles and duties as teachers who are committed, competent, creative, and compliant. Training and seminars on gender mainstreaming issues may be strengthened to foster gender-responsive schools toward safe and inclusive spaces for LGBT teachers.